Heparin-Induced Thrombocytopenia Platelet Aggregation Studies in the Presence of Heparin Fractions or Semi-Synthetic Analogues of Various Molecular Weights and Anticoagulant Activities - Blockmans, D; Bounameaux, H; Vermylen, J; Verstraete, M (Thrombosis and Haemostasis, 1986)
One case of heparin-induced thrombocytopenia is reported. Aggregation was observed in the platelet-rich plasma of this patient in the presence of two commercial standard heparin preparations (from a final concentration of 0.025 IU/ml upwards), of two semi-synthetic heparin analogues (0.1 APTT U/ml) and of three low-molecular weight heparin (LMWH) fractions (0.1 anti-Xa U/ml) but not in the presence of five other LMWH fractions.The patient’s isolated platelets no longer aggregated in the presence of heparin but the phenomenon recurred after addition of the patient’s platelet poor plasma (PPP).Furthermore, addition of patient’s PPP to control platelets led to heparin-induced aggregation.The phenomenon was associated with thromboxane generation and could be blocked by in vitro addition of aspirin, PGI2, and PGD2 whereas the lag phase was dose-dependently prolonged by adenosine.It is concluded that platelet aggregation may be induced in some patients by standard heparin and by certain LMWH fractions or semi-synthetic analogues, independently of their molecular weight and anticoagulant activity.
Keywords: Heparin-induced thrombocytopenia; Low molecular weight heparin; Semi-synthetic heparin analogues; Arachidonic acid pathway